MO920TRANSITION FROM GENERIC TO BRAND TACROLIMUS IN TUNISIAN RENAL TRANSPLANT RECIPIENTS. (29th May 2021) - Amor, Dorra; Wissal, Sahtout; Ellouz, A; Abderrahman, Ameni; Azzabi, Awatef; HadjBrahim, Mayssa; Mrabet, Sanda; Fradi, Asma; Ben Aicha, Narjes; Zallema, Dorsaf; Sabri, Ferdaous; Omezzine, Asma; et al.
Abstract: Background and Aims: Due to unavailability of the generic tacrolimus, commonly used in renal transplant patients in Tunisia, all renal transplant switched to the Brand. No previous studies have assessed the pharmacokinetic differences of this generic tacrolimus compared to the brand. The aim of the present study was to evaluate the effect of this switch on the tacrolimus dose (D) and on the dose-adjusted tacrolimus trough blood concentrations (C0/D) in Tunisian renal transplant recipients. Method: For the 255 renal transplant monitored in biochemestry department of Sahloul University hospital, 808tacrolimus trough concentration (C0) were collected from october 2018 to February 2020 and were divided to 406 C0 determination before switch and 402 after switch. The dose and the post-transplantation period was recorded for each C0. Results: The generic tacrolimus doses used were significantly higher compared to the brand: 0, 12 mg/kg [0, 02-0, 6] vs 0, 11 mg/kg [0, 02-0, 22] p<0, 001 and this was reported in different post graft periods: 0, 17 [0, 03-0, 22] vs 0, 13 [0, 06-0, 22] p<0, 001in the 3 first months after the transplantation and 0, 11 [0, 02-0, 48] vs 0, 08 [0, 02-0, 22] p<0, 001 above.The C0/D were significantly lowe runder the the generic tacrolimus compared to the brand 48, 34ng/ml per mg/kg/day [11, 58-210, 00] vs77, 35ng/ml per mg/kg/day[19, 38-221, 67]; p<0, 001 and this was reported in different post graft periods: 71, 12ng/ml per mg/kg/day [6, 80, 451, 56] vs80, 9750ng/ml per mg/kg/day [17, 33-458, 80] p=0, 017 in the 3 first months after the transplantation and 71, 12ng/ml per mg/kg/day [6, 80, 451, 56] vs80, 9750ng/ml per mg/kg/day [17, 33-458, 80] p=0, 017 above. Dose needed to reach target tacrolimus C0 seems to be higher with the generic tacrolimus compared to the brand. Conclusion: Approval of a generic is dependent on bioequivalence testing in healthy adult volunteers after a single dose, however studies on renal graft recipient populations after chronic use are needed to assed bioequivalence in this special population.